External cephalic version at term: A 6‐year single‐operator experience. Issue 4 (2nd April 2019) - Levin, Gabriel; Rottenstreich, Amihai; Weill, Yishay; Pollack, Raphael N.
Abstract: Background: External cephalic version (ECV) should be offered for patients presenting with a noncephalic pregnancy that are willing to deliver vaginally. Various reports have evaluated predictors for successful ECV. Yet, none have reported a single‐operator large cohort experience. We aim to analyze the outcome of referrals for ECV. Methods: We conducted a retrospective cohort study of prospectively collected data. We performed a multivariate analysis of data with respect to ECV procedures performed by a single operator in a 6‐year period. Maternal and fetal characteristics were compared between ECV success and failure groups. Results: Six hundred and two women underwent ECV. Of them, ECV was successful in 432 (71.7%). A multivariate binary logistic regression model demonstrated that high liquor volume was a predictor of ECV success (Adj OR 1.17 [95% CI 1.09‐1.26]). Failure of ECV was correlated with anterior placenta (0.44 [0.56‐0.76]) and nulliparity (0.21 [0.11‐0.36]). Adverse events were rare and mostly minor, occurring in 1% of procedures. Conclusions: ECV has a high success rate and a low complication rate, enabling vaginal birth and avoiding cesarean. The role of manipulation of modifiable determinants such as liquor volume should be further assessed in future studies.